2017
DOI: 10.1111/ger.12292
|View full text |Cite
|
Sign up to set email alerts
|

Can grip strength and/or walking speed be simple indicators of the deterioration in tongue pressure and jaw opening force in older individuals?

Abstract: Decreased swallowing-related muscle strength can be inferred in cases involving male patients for whom decreased grip strength is measured during physical examination or is otherwise suggested (eg, by an inability to open plastic bottles).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 26 publications
0
47
1
4
Order By: Relevance
“…In this study, we showed that tongue pressure had a close association with handgrip strength in both men and women. Previous studies investigated the association between tongue pressure and sarcopenia; however, many of them did not consider sex differences of tongue pressure and handgrip strength, and few studies evaluated the relationship between tongue pressure and handgrip strength in men and women, separately . The present results showed that the correlation between tongue pressure and handgrip strength, which indicated muscle power and function, was higher than the correlation between tongue pressure and SMI, which indicated muscle mass.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, we showed that tongue pressure had a close association with handgrip strength in both men and women. Previous studies investigated the association between tongue pressure and sarcopenia; however, many of them did not consider sex differences of tongue pressure and handgrip strength, and few studies evaluated the relationship between tongue pressure and handgrip strength in men and women, separately . The present results showed that the correlation between tongue pressure and handgrip strength, which indicated muscle power and function, was higher than the correlation between tongue pressure and SMI, which indicated muscle mass.…”
Section: Discussionmentioning
confidence: 98%
“…Grip strength and walking speed are associated with tongue pressure and to a lesser extent jaw opening force in men (62)(63)(64)(65)(66)(67)(68). Similarly, head lifting strength is associated with dysphagia and malnutrition in older persons (69).…”
Section: The Frailty Phenotype and Dysphagiamentioning
confidence: 99%
“…Sarcopenia defined by low SMMI and grip strength at the hospital, physical frailty, frailty, advancing age, history of clinical disease, loss of SMM, and handgrip strength have been found to be associated with dysphagia among older individuals in several settings (1,4,(28)(29)(30)(31)(32). Besides, tongue pressure was related to grip strength and gait speed in males, and head lifting strength was related to dysphagia and poor nutritional status among older patients where EAT-10 was associated with nutritional status at long term care (33)(34)(35). Likewise, dysphagia risk by EAT-10 was higher in patients with malnutrition, low SMMI, in the older ages, hospitalizations with pneumonia in the past year, and prescription of modified diet, but not in the participants with low grip strength, and the presence of diseases and hospitalizations in one year, in this study.…”
Section: Discussionmentioning
confidence: 98%